2014
DOI: 10.1111/aas.12445
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal dexmedetomidine in combination with patient‐controlled sedation during upper gastrointestinal endoscopy: a randomised trial

Abstract: Intranasal dexmedetomidine with PCS propofol and alfentanil confers deeper perioperative clinical sedation with significantly less use of additional sedatives during upper gastrointestinal endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 31 publications
3
24
0
1
Order By: Relevance
“…In Cheung's study, intranasal dexmedetomidine 1.5 μg/kg with patient-controlled-sedation (PCS) of propofol and alfentanil offered deeper perioperative clinical sedation with significantly less use of additional sedatives during upper gastrointestinal endoscopy [11]. Similarly, in our study, consumption of propofol in group DP was significantly lower than that in group P and group SP (P<0.001 and P<0.01, respectively).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In Cheung's study, intranasal dexmedetomidine 1.5 μg/kg with patient-controlled-sedation (PCS) of propofol and alfentanil offered deeper perioperative clinical sedation with significantly less use of additional sedatives during upper gastrointestinal endoscopy [11]. Similarly, in our study, consumption of propofol in group DP was significantly lower than that in group P and group SP (P<0.001 and P<0.01, respectively).…”
Section: Discussionsupporting
confidence: 62%
“…Dexmedetomidine has been used as a sedative agent in intensive care unit and an anesthetic adjunct in surgery [7][8][9]. Recently, more and more studies propose it as a sedative agent in moderate sedation for clinical surgeries/procedures [10][11][12][13]. Intravenous infusion of dexmedetomidine is commonly used, but rapid administration or bolus might cause bradycardia and hypotension [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…formulation is also efficacious when administered by the intranasal route in both children 4e8 and adults. 9,10 Since this is not associated with any unpleasant sensation, there is increasing use for paediatric premedication and procedural sedation. 5,11 There is one report on the bioavailability (65%) of intranasal dexmedetomidine in healthy volunteers, 12 performed with a special nasal pump and a highly concentrated veterinary formulation of dexmedetomidine (84 mg in 0.2 ml).…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…11 Intranasal DEX is convenient, effective, noninvasive, and also has useful analgesic and sedative effects in surgical procedures. 12,13 Cheung's research has shown that intranasal DEX 1 and 1.5 μg/kg in surgical procedures produced significant sedation and less postoperative pain. 13,14 DEX has vasoconstrictive effects on peripheral blood vessels.…”
Section: Introductionmentioning
confidence: 99%